Densidades populacionais e espaçamentos duplos de dois híbridos de tomate para processamento industrial no cerrado goiano - Silva, Sheila Izabel da (2014)
The combined utilization of plants density and spacing among rows is a technology that aim at efficient exploration of environment growing for any crop. The aim was compare the spatial arrangements among double rows of plants industrial tomato hybrids (H-9553 and N-901), in spacings 1,2 m and 1,3 m, in populations 25, 30 and 35 thousand plants ha-1. The assays were conducted in season 2012 at experimental field of Cargill Foods at Aparecida de Goiania, Goias, Brazil (16º 52’S, 49º 18’W, 804m altitude) and in season 2013 in Agronomy School, Federal University of Goias, Goiania, Goias, Brazil (16º 35’S, 49º 21’ W, 727m altitude). The experimental design was in randomized block in split-plots, with four replicates, being the main plot represented by factorial between population densities (25.000, 30.000 and 35.000 plants ha-1) and spacings among double rows (1,2m and 1,3m), and the subplots by two hybrids. The variables evaluated were yield, maturation percentage, soluble solids content (ºBrix), mass of ten fruits, diameter and length of industrial tomato hybrids (H-9553 and N-901). The characters that isn’t showed differential responses were: maturation percentage, mass of ten fruits, in seasons 2012 and 2013, and yield, diameter and length, in season 2013. For yield, only in season 2012 there was a differential response (P < 0,10) to the three population densities, a estimated increased of 5,6 t ha-1 each five thousand plants addition. For the same season there was significant difference (P < 0,10) to ºBrix between levels of population density within each spacing. While in season 2013 the same variable was the only that showed significant difference (P < 0.10) for the source of hybrid variation wherein N-901 (5.35), on average, showed fruit with higher ºBrix than that H-9553 (5.20). Regarding at lenght and diameter, only season 2012, there was difference for the source of hybrid variation (P < 0,05) and spacing (P < 0,10). The N-901 hybrid obtained the higher content ºBrix in both seasons, length and diameter (season 2012) than H-9553 when submitted at spacing 1,3m among double rows in population density of 35 thousand plants ha-1.